Pengelolaan Fasilitas Serta Prasarana dalam Meningkatkan Proses Pembelajaran Peserta Didik dI SMAN 1 Sumber - Sri Handayani, Sri Handayani (IAIN Syekh Nurjati Cirebon, 2022)
The facilities and infrastructure owned by SMA 1 Sumber in Cirebon district, can be said to be quite adequate, but there are shortcomings in school conditions such as the wide environment at SMAN 1 SUMBER making facilities poorly maintained at several points, especially the Labs and Mosques at SMAN 1 Sumber . This can be minimized by means of community service for the entire community of SMAN 1 SUMBER, of course this can maintain the condition of the facilities at SMAN 1 SUMBER well maintained, so that they are not easily damaged. And also during the Covid-19 pandemic which has been running for more or less two years, conditions at some points in SMAN 1 Sumber are not well maintained, especially when students pass through the SMAN 1 SUMBER mosque, which looks very dirty with thick leaves and dust. This affects learning activities and the learning process is less effective and efficient. Management of facilities and infrastructure in improving the learning process at SMAN 1 SOURCE school includes planning, organizing, procurement and supervision. To conduct a selection of the items to be used, it means that the manager checks the items that support the learning process, to avoid unwanted mistakes. The teacher's efforts to improve the learning process of students at SMAN 1 SUMBER, the teacher's obstacle in improving the learning process of students is the limited cleaning of facilities and facilities at SMAN 1 Sumber. Supporting and inhibiting factors in improving the learning process of students at SMAN 1 Sumber, Cirebon district, as for the supporting factors, one of which is the teacher, the teacher's role is very important for the learning process, because professionalism will determine success during the teaching and learning process in the classroom. . The management of learning facilities and infrastructure plays a significant role in distributing donations optimally in the course of the learning process so that it can produce clean, neat and beautiful schools so as to produce an exciting and safe environment for both teachers and students to be in school. In addition, it is hoped that there will be tools and equipment or learning facilities that are sufficient quantitatively, qualitatively and relevant to the needs and can be utilized optimally for the benefit of the learning and education process for both teachers and students. The process of increasing at SMA N 1 Sumber, Cirebon Regency, can be seen from the number of students who enter every year.